Pilot scale soda-anthraquinone pulping of palm oil empty fruit bunches and elemental chlorine free bleaching of resulting pulp. (1st November 2015) - Sharma, Arvind Kumar; Anupam, Kumar; Swaroop, Vinay; Lal, Priti Shivhare; Bist, Vimlesh
Abstract: Development of large scale commercial pulping and papermaking processes using agricultural solid residues as raw materials is ecologically and environmentally important. This paper reports pilot scale soda-anthraquinone pulping of palm oil empty fruit bunches and elemental chlorine free bleaching of resulting pulp using DEpD sequence. The physical and morphological properties of resulting bleached and unbleached pulp fibres along with yield have been determined. The pilot scale unbleached pulp exhibited brightness 31.4%, kappa number 18, viscosity 845 mL/g, tensile index 59 Nm/g, burst index 5 kN/g and tear index 7.8 mNm 2 /g with a yield of 48% and bleached pulp resulted in brightness 85%, viscosity 650 mL/g, tensile index 48 Nm/g, burst index 4.70 kN/g and tear index 9.1 mNm 2 /g. Comparison of these values with those obtained at lab scale by various researchers through different processes revealed that the operating conditions adopted in this study can be successfully implemented at a paper mill for commercial production of pulp and paper from palm oil empty fruit bunches. Highlights: Pilot scale pulping of palm oil empty fruit bunches. DEpD bleaching of soda-anthraquinone pulp. Pulp fibre morphology and characteristics. Pulp physical and strength properties. Comparison with data collected from literature.